2016
DOI: 10.21522/tijar.2014.03.01.art005
|View full text |Cite
|
Sign up to set email alerts
|

Study of Association between Psychological Stress and Depression among Undergraduate Medical Students from Asia Metropolitan (Amu) in Johor Bahru

Abstract: Background:Stress is a term that refers to the sum of physical, mental and emotional strains or tensions on a person. Depression is a common mental disorder that presents with depressed mood, loss of interest or pleasure, decreased energy, feelings of guilt or low selfworth, disturbed sleep or appetite, and poor concentration. Psychological Stress among medical students is common as compared to other professional courses. The aim of the study is to study the association between Psychological Stress and Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This finding was similar to a study done by Kittu and Kumar. 13,15 In this study, females have high prevalence of psychological stress (87.3%) and depression (76.3%) compared to males, which was also observed in a study by Marzo et al and Kumar et al 14,15 In this study, depression was higher among 1 st year of medical students compared to other years of study. However, Rawat et al also showed the prevalence of depression among 1 st year student was 72.6%, which was similar to our study findings.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This finding was similar to a study done by Kittu and Kumar. 13,15 In this study, females have high prevalence of psychological stress (87.3%) and depression (76.3%) compared to males, which was also observed in a study by Marzo et al and Kumar et al 14,15 In this study, depression was higher among 1 st year of medical students compared to other years of study. However, Rawat et al also showed the prevalence of depression among 1 st year student was 72.6%, which was similar to our study findings.…”
Section: Discussionsupporting
confidence: 76%
“…There are very few documented studies to establish association between psychological stress and depression among medical students. 13,14 In this study, BDI was used to assess the prevalence of depression among medical students and the prevalence of depression was 72.9%. In a study done by Kittu, the prevalence of depression among medical student in Pondicherry was 71%, which was similar to our finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress is a commonly used word that often refers to the sum of physical, mental and emotional tensions on a person (Marzo et al, 2016). Each person undergoes stress in different forms.…”
Section: Introductionmentioning
confidence: 99%